2020
DOI: 10.1002/app.49561
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical inspection of polypyrrole/chitosan/zinc oxide hybrid composites

Abstract: Polymer nanocomposite composed of polypyrrole, chitosan, and zinc oxide nanoparticles has been synthesized and it has been evaluated for various electrochemical aspects of the current electrochemical industry. The polypyrrole (PPy) was synthesized by the chemical oxidative polymerization reaction by employing ammonium persulfate as oxidizing agent. Composites of polypyrrole/chitosan (PPy/Chy) and polypyrrole/chitosan/ZnO (PCZ) composites were synthesized by the solution blending method. Detailed structural, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 75 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Thermogravimetric analysis (TGA) of the samples was performed under N 2 atmosphere by raising the temperature from room temperature to 600 ˚C. Figures (4) 25 . The increase in the temperature from 177 ˚C to around 282 ˚C resulted in an increase in weight loss due to the condensation dehydration of the hydroxyls 25 .…”
Section: Thermal Properties Of the Prepared Materials (Tga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Thermogravimetric analysis (TGA) of the samples was performed under N 2 atmosphere by raising the temperature from room temperature to 600 ˚C. Figures (4) 25 . The increase in the temperature from 177 ˚C to around 282 ˚C resulted in an increase in weight loss due to the condensation dehydration of the hydroxyls 25 .…”
Section: Thermal Properties Of the Prepared Materials (Tga)mentioning
confidence: 99%
“…However, polypyrrole suffers from some shortcomings such as poor mechanical features and chemical sensitivity leading to poor processibility [3]. The compositing between polypyrrole and other materials (e.g., ZnO, cellulose acetate) can overcome its processibility shortage and increase its stability, sensitivity and biomolecule immobilization of the biosensor 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for detection of various bio-analytes in human blood including glucose [4], cholesterol [5], H 2 O 2 [6], urea [7], DNA [8], etc. Recently, ZnO finds great applications in development of reagentless biosensors by doping [9], forming p-n junction heterostructures [1], or making hybrid composites [10]. Wu et al [11] have reported a photoelectrochemical and self-powered biosensor based on p-n junction of ZnO and Cu 2 O. Uddin et al [12] have reported the development of a chemisensor based on GCE modified with ZnO/RuO 2 NPs for detection of 2nitrophenol in different water samples.…”
mentioning
confidence: 99%